The level of political conservatism of barangay officials of Dulag, Leyte. - Caminong, Leah, et al.; Estil, Sheikha Kaye C. (Tacloban City Leah Caminong, 2010)
Dulag is a third-class municipality, dominated by Roman Catholics. Given this, it is a rural community which may have difficulty in accepting liberal ideas and change in political values. Hence, it is a very ideal locale for the study of political conservatism. Political conservatism refers to the extent of one's resistance to political changes, thus, characterized by traditionalism, pragmatism, property, hierarchy and authority.
This is a descriptive study conducted to determine the level of political conservatism of barangay officials of Dulag, Leyte and how this level is influenced by the barangay officials' socio-economic and demographic characteristics. The levels of political conservatism were expressed through arithmetic means. And the relationships between variables were measured using eta correlation, and p-value.
The results revealed that majority of the barangay officials are males, married, mostly aged between 39 to 48 years, have at least attended College, vendors, earn 20,001 to 30,000 pesos annually, and all are Roman Catholic. Overall, all barangay officials all rated themselves as conservatives. It was further observed that the barangay officials' rating of their own personal level of political conservatism was consistent with the ratings given by their respective legal-aged constituents.
The barangay officials' level of political conservatism was not influenced by their age, sex, civil status, educational attainment, previous work employment and length of incumbency. However, there was a significant relationship between the level of political conservatism and their level of income. Notwithstanding, barangay officials recognize the implication of their level of political conservatism on barangay governance. Conservative attitudes do influence the way these barangay officials would make decisions on political, social and economic issues that affect the community.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science